Ileal Digestible and Metabolizable Energy of Corn, Wheat, and Barley in Growing Japanese Quail - Sousan Khanipour; Mahmoud Ghazaghi; Mohammad Reza Abdollahi; Mehran Mehri (Poultry)
This study aimed to determine the ileal digestible energy (IDE), apparent metabolizable energy (AME), and nitrogen-corrected AME (AMEn) of three typical cereals for quail chicks with two age periods (day 15–21 and 22–28). The experimental diets comprised a corn–soybean meal reference diet (RD), and three test diets (TD) that were fed to quail chicks in a completely randomized design with five replicates per diet and 15 birds each. The TD comprised corn, wheat, and barley that partly replaced the RD at 300 g/kg (70% reference diet + 30% test ingredient). Age did not influence the IDE, AME, and AMEn values, while the effect of ingredient type was highly significant on the energy estimates (p < 0.001). The IDE values of corn, wheat, and barley were estimated as 2924, 3440, and 3184 kcal/kg, respectively. The AME values of corn, wheat, and barley were 3519, 2979, and 2710 kcal/kg, respectively. The estimated AMEn values of corn, wheat, and barley were 3483, 2903, and 2532 kcal/kg, respectively. These findings are crucial for optimizing diet formulations to support quail growth and performance effectively, as they provide valuable insights into the energy content of different cereals for quail production. Notably, the high IDE and AME values of wheat suggest its potential as a valuable energy source for quail diets. Understanding these values can aid in formulating diets that meet the energy requirements of quail chicks, leading to improved growth rates, feed efficiency, and overall productivity in quail production systems.